PENGARUH TEMUAN AUDIT DAN TINDAK LANJUT REKOMENDASI AUDIT TERHADAP KUALITAS PELAYANAN PUBLIK MELALUI KUALITAS LAPORAN KEUANGAN (Studi Empiris pada LKPD Kabupaten Daerah Tertinggal di Indonesia Tahun 2016-2017) - Aulia Dwi Lestari; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of Audit Findings and Audit Recommendation Follow-up on the Quality of Public Services through Quality of Financial Report in underdeveloped districts in Indonesia according to the Attachment of Presidential Regulation No. 131 of 2015. The independent variables used in this study are Audit Findings and Audit Recommendation Follow-up. This study uses secondary data in the form of local government financial report obtained through the Supreme Audit Agency (BPK). This research uses purposive sampling. The sample of this study consisted of 22 underdeveloped districts in Indonesia according to Presidential Regulation Number 131 of 2015 in the period of 2015-2019.The analysis model of this research uses Partial Least Square-SEM analysis. This study shows two effects of independent and dependent variables that will be tested direct and indirectly. The results of the study indicates that the Audit Findings and Audit Recommendation Follow-up do not direct and indirectly affect the quality of public services.